Canine distemper virus in a crab-eating fox (Cerdocyon thous) in Brazil: case report and phylogenetic analyses - Megid, Jane [UNESP]; Feijo de Souza, Vanessa Aparecida [UNESP]; Teixeira, Carlos Roberto [UNESP]; Cortez, Adriana; Amorin, Renee Laufer [UNESP]; Heinemman, Marcos Bryan; Cagnini, Didier Quevedo [UNESP]; Richtzenhain, Leonardo Jose (Wildlife Disease Assoc, Inc, 2009)
Although canine distemper is enzootic worldwide and has a wide host range, there are no reports of canine distemper virus there are no reports of canine distemper virus provide information on virus phylogeny and histopathologic lesions. The objective of this study is report and describe canine distemper in a crab-eating fox (C. thous), with a focus oil the phylogeny of the virus strain and the histopathologic lesions in the animal.
Keywords: Cerdocyon thous; clinical signs; histopathology; nervous system; virus phylogeny